2005
DOI: 10.1080/15438620500222547
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of Proprioceptive and Balance Training after Surgical Reconstruction of the Anterior Cruciate Ligament

Abstract: A randomised controlled trial (29 participants) was used to compare a 6-week proprioceptive and balance exercise program with a 6-week strengthening program in the early phases of rehabilitation after anterior cruciate ligament (ACL) reconstruction. Measurements of functional activity were taken by a blinded assessor before the intervention and at the end of the 6 weeks. Results demonstrated that there were no significant differences between groups on hop testing at 6 weeks. For several items in the Cincinnati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 24 publications
5
79
0
3
Order By: Relevance
“…Cooper et al compared six weeks of strength training with proprioceptive and balance training in twenty-nine randomized patients 26 . Patients were evaluated on the basis of the Cincinnati knee score, patient-specific functional scale, knee motion, and hop test after completion of the six weeks of treatment.…”
Section: Neuromuscular Trainingmentioning
confidence: 99%
“…Cooper et al compared six weeks of strength training with proprioceptive and balance training in twenty-nine randomized patients 26 . Patients were evaluated on the basis of the Cincinnati knee score, patient-specific functional scale, knee motion, and hop test after completion of the six weeks of treatment.…”
Section: Neuromuscular Trainingmentioning
confidence: 99%
“…The Gulhane ACL Rehabilitation Protocol is a more comprehensive neuromuscular training model than that reported by Risberg et al, Cooper et al, Fitzgerald, Ihara, Beard, and Lui-Ambrosso et al (4,7,13,(16)(17)(18)(19). Optimal healing of the ACL is dependent on rehabilitation.…”
Section: Discussionmentioning
confidence: 72%
“…Despite some limitations in these studies, they all showed significantly improved knee function with the use of rehabilitation programs that included neuromuscular exercises, as compared to only strength training exercises in patients with ACL deficiencies. Only a very limited number of controlled trials on the effects of neuromuscular training after ACL reconstruction have been reported (16,17). None of these studies provide baseline data (pre-operative data) and all have major limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proprioceptive acuity is defined by Muaidi, Nicholson and Refshauge (2008, p.371) as "the ability to sense joint positions, movement and force of muscle contraction and to discriminate movements of limb segments individually and relative to each other". The bulk of the research on proprioceptive acuity has examined differences in proprioceptive acuity after injury or surgery (Cooper, Taylor, & Feller, 2005;Fischer-Rasmussen & Jensen, 2000) or during rehabilitation (Cooper et al, 2005). One approach that has been widely used in a clinical setting to establish perceivable difference is the "just noticeable difference" (JND) method.…”
Section: Kinaesthetic Sensitivity For Movement Pattern Informationmentioning
confidence: 99%